Investigating STEM Students’ First-Time Experience with Smart Glasses - Santana, Ronny (2022)
We study how STEM students experience the use of smart glasses for the first time. We evaluate the glasses’ usability, degree of technological acceptance, experience, and elicited emotional response. To this end, we resort to several quantitative instruments and semistructured interviews. We found that students greatly appreciate the potential and current support that smart glasses and AR provide as educational tools. We discuss our findings and identify opportunities for further research with these devices to support educational activities.